2021
DOI: 10.3390/v13061073
|View full text |Cite
|
Sign up to set email alerts
|

Full-Genome Sequences of Alphacoronaviruses and Astroviruses from Myotis and Pipistrelle Bats in Denmark

Abstract: Bat species worldwide are receiving increased attention for the discovery of emerging viruses, cross-species transmission, and zoonoses, as well as for characterizing virus infections specific to bats. In a previous study, we investigated the presence of coronaviruses in faecal samples from bats at different locations in Denmark, and made phylogenies based on short, partial ORF1b sequences. In this study, selected samples containing bat coronaviruses from three different bat species were analysed, using a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 80 publications
(125 reference statements)
2
19
0
Order By: Relevance
“…Genomebased and functionalgene-based phylogeny constructions also indicated that this strain formed a separate branch in phylogenetic trees (Figures 4 and 5). Recent metagenomic studies of bat virome revealed potential novel species within Alphacoronavirus detected in bats around the world [27,[48][49][50]. This result, along with other up-to-date studies, once again supported the genetic heterogeneity of this genus.…”
Section: Discussionsupporting
confidence: 62%
“…Genomebased and functionalgene-based phylogeny constructions also indicated that this strain formed a separate branch in phylogenetic trees (Figures 4 and 5). Recent metagenomic studies of bat virome revealed potential novel species within Alphacoronavirus detected in bats around the world [27,[48][49][50]. This result, along with other up-to-date studies, once again supported the genetic heterogeneity of this genus.…”
Section: Discussionsupporting
confidence: 62%
“…About 1-2 million reads that mapped to the ASFV genome were analyzed here from each of the inoculated pigs at 6 dpi. Another advantage obtained from selecting the poly(A)+ mRNA is that reads derived from residual ASFV DNA should be further diminished beyond that achieved by DNAseI treatment alone, which may not be completely effective [32]. However, some reads may be derived from residual ASFV DNA (there are only short regions of the genome that are not included in any reads), along with other incompletely digested host DNA, e.g., pig mitochondrial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The novel Swedish alpha-CoV sequence formed a cluster, mainly with other alpha-CoVs isolated from M. daubentonii. The sequence was highly similar to full-length viral genome sequences from M. daubentonii from Denmark [12] and Finland [13]. Within the cluster, there were relatively closely related alpha-CoV sequences from other bat species, one from a Danish alpha-CoV detected in Pipstrellus pygmaeus in Denmark, 2014, and another from a Miniopterus shreibersii in China, 2021 [33] (Figure 3).…”
Section: Discussionmentioning
confidence: 89%
“…This was the first report of coronavirus presence in bats in Sweden, while it has previously been found in Denmark, Finland and other European countries [11][12][13]. For detection and sequencing of the coronavirus, we used a method comprising next-generation sequencing with virus-specific targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation